Alcances, limites e contradiç\~oes nos termos de troca entre as economias do centro-oeste brasileiro e seus parceiros comerciais: O caso do bloco econômico de China, Hong Kong e Macau - Murilo José de Souza Pires (Instituto de Pesquisa Econômica Aplicada (IPEA), 2023)
– The central point of the investigation was to verify the extent to which trade flows between the Midwest region and its trading partners have modified the structure of the terms of trade between them, in particular, in relation to the economic bloc of China, Hong Kong and Macau in the period between 1998 and 2021. In this sense, it appears that the ratio between the values of exports from the Center-West region to the rest of the world vis-à-vis aggregate imports, between 1998 and 2021, did not show, in any way, apparent form, signs of deterioration in the terms of trade. However, it is important to point out that, since 2009, there has been an upward cycle in the prices of agricultural commodities and metals, which is possibly influencing, in a positive way, so that there is no deterioration in the terms of trade between the Midwest region and the other business partners. On the other hand, when one observes the ratio between exported values of basic products vis-à-vis imports of manufactured products between the Center-West region and the rest of the world, in the period 1998 and 2021, the same can be seen apparent phenomenon highlighted for aggregate exports and imports. In this way, a more hasty analysis could indicate that the Prebisch-Singer hypothesis would be refuted for the specific case of the Midwest region and its trading partners in the given historical period. However, it is important to point out that, when verifying the structure of the terms of trade between the countries involved, there is a high concentration of basic products in the export basket of the Central-West region, as well as a high concentration of manufactured products in the import basket. As they are products that present different natures of industrialization, then, one can raise the imperative hypothesis, that this is happening under the influence of favorable price cycles of agricultural and mineral commodities. Therefore, it was decided to deepen the analysis a little more and verify the behavior of the terms of trade between the Midwest region and its main trading partner, the economic bloc China, Hong Kong and Macau. Therefore, it is important to highlight that the nature of the Chinese development style is different from that seen in the Midwest region. Even though both have projected the impulses of their economic growth to international markets, even so, the Chinese economy implemented an active industrial policy that was based on a revolution in its industrial structure through the increasing use of Science, Innovation and Technology. In this way, the Chinese strategy was to increasingly boost its role in the international division of labor with products with higher added value, that is, manufactured products, in particular those related, in the first instance, to the 3rd Industrial Revolution and, more recently, with the 4th Industrial Revolution. That said, the Chinese expansion strategy for the economies of Latin America, Africa and Asia has intensified, in particular, through the export of manufactured goods. It is in this context that commercial transactions between the Center-West region and the Chinese economy will take place between 1998 and 2021. In this way, the ratio between exports of basic products from the Center-West region vis-à-vis Imports of manufactured products from the economic bloc of China, Hong Kong and Macau, between 1998 and 2021, have been showing an average growth rate of -1.8% p.a. In addition, the ratio between basic exports and manufactured imports between these regions declined from almost 20 times in 2000 to just over 6.5 times in 2021. All of this is a clear sign that, even with an upward price cycle of agricultural commodities and metals, there is a deterioration in the terms of trade between the Center-West region and the economic bloc of China, Hong Kong and Macau which, in the long term, may bring strong restrictions to the economic growth of the Center-West.
Keywords: R11; 330; terms of trade; midwest economy; China